A DATA-DRIVEN APPROACH FOR CREATIVE CONCEPT GENERATION AND EVALUATION. (May 2020) - Han, J.; Forbes, H.; Shi, F.; Hao, J.; Schaefer, D.
Abstract: Conceptual design, as an early phase of the design process, is known to have the highest impact on determining the innovation level of design results. Although many tools exist to support designers in conceptual design, additional knowledge, especially knowledge related to emerging technologies, is still often needed. In this paper the authors aim to propose a data-driven creative concept generation and evaluation approach to support designers in incorporating emerging technologies in the new product early development stage. The approach is demonstrated by means of an illustrated example.